PENGARUH PENDAPATAN ORANG TUA DAN LITERASI EKONOMI TERHADAP MINAT BERWIRAUSAHA PADA SISWA SMK SANTA MARIA PONTIANAK - Valensya, Arini Bella; Warneri, Warneri; Syahrudin, Husni (Universitas Tanjungpura, 2025)
The study aims to know (1) The influence of parental income on entrepreneurial interest in Santa Maria Pontianak SMK students (2) The influence of economic literacy on entrepreneurial interest in Santa Maria Pontianak SMK students (3) The influence of parental income and economic literacy on entrepreneurial interest in Santa Maria Pontianak SMK students. The subject of this study was X and XI students who numbered 187 with research objects conducted at Santa Maria Pontianak SMK. The data collection technique in this study uses hacket and documentation with sampling techniques using simple random sampling. The method used is a form of quantitative research with correlational results. The instrument test used consists of validity test and reliability test. The data analysis used is classical assumption test, hypothesis test, multiple linear regression analysis. The results of this study showed the magnitude of the coefficient of determination (R2) of 0.490 so that it can be concluded that the magnitude of the influence of parental income variables (X1) and economic literacy (X2) on the rise or variation of the value or variables of entrepreneurial interest in Santa Maria Pontianak students is 49.0% while 51.0% is affected by other variables other than variables in this study. Furthermore, the results of the simultaneous test value of 0.000 and because it is smaller than the trust level value of 0.05, so it can be concluded that there is a significant influence of parental income variables and economic literacy simultaneously affects entrepreneurial interest in Santa Maria Pontianak SMK students.